EVALUATION OF BIOCHEMICAL MARKERS OF BONE TISSUE METABOLISM WHEN USING OSTEOTROPIC MATERIAL IN DENTAL IMPLANTATION (World Bulletin of Public Health, 2025)
Optimization of osseointegration conditions in dental implantation by introducing calcium-based bone tissue regeneration stimulants into the body to improve the effectiveness of treatment of patients with dental defects
Keywords: Dental Implantation; Dental Defects